KEBERADAAN TRANSPORTASI DARAT:STUDI KASUS BUS MANDALA PASAMAN BARAT TAHUN (1981-2009) - Handayani, Resti; Nurhuda, Ahmad; Meldawati, Meldawati (Pendidikan Sejarah, 2013)
ABSTRACT This thesis is a study of the history of transportation in the title Presence Ground Transportation: Case Study Mandala Suites West Pasaman years ( 1981-2009 ). The formulation of the problem in this research is how the presence of PO Mandala as freight transportation field - Pasaman PO Mandala and how developments in the 1981-2009 timeframe .This research includes the study of history, historical method has four steps, namely heuristic which is the stage of data collection in both primary and secondary. Further criticism of the sources of the test obtained. Interpretation of data relating to according to the theme discussed. The final stage of the historiography of the research results in the form of writing a thesis.From these results obtained that the PO. Mandala is a public transport freight Padang- Pasaman that has been operating for 32 years. Although strict competition in the field of transportation PO. Mandala still remain and survive as transport transporasi Padang- Pasaman. PO Mandala is one of the public transport that can survive in the midst of tight competition existing transportation advice in Pasaman. Mandala PO using the combined system is open from 1982.Â Keywords: Transport, Transport Services, Corporate outo ( PO )